Dualisme Judicial Review Peraturan Perundang-Undangan di Indonesia - Hidayat, Nanang Al; Sari, Mela (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 7 No 3 (2018)DO - 10.24843/JMHU.2018.v07.i03.p04, 2018)
Based on the provisions of Article 24A paragraph 1 of the 1945 Constitution and Article 24C paragraph 1 of the 1945 Constitution, there is a dualism of judicial institutions authorized to decide the judicial review of conflict of laws and regulations, namely the Supreme Court and the Constitutional Court. This study aims to find out how to regulate the judicial review of legislation in Indonesia. The research method used in this paper is the normative juridical. The results of the study showed that the dualism of statutory regulatory bodies resulted in inconsistencies in providing decisions related to the prevailing laws and regulations in Indonesia. Whereas legislation is arranged hierarchically and has a proportion of certain content material that must be tested consistently in one institution only to provide a legal certainty for the community. Berdasarkan ketentuan dalam Pasal 24A ayat 1 UUD 1945  dan Pasal 24C ayat 1 UUD 1945 terjadi dualisme lembaga kehakiman yang berwenang memutus judicial review konflik peraturan perundang-undangan yaitu Mahkamah Agung dan Mahkamah Konstitusi. Penelitian ini bertujuan untuk mengetahui bagaimana pengaturan judicial review peraturan perundang-undangan di Indonesia. Metode penelitian yang digunakan dalam tulisan ini adalah yuridis normatif. Hasil penelitian menunjukan dualisme lembaga pengujian peraturan perundang-undangan menyebabkan inkonsistensi dalam memberikan putusan terkait permasalahan peraturan perundang-undangan yang berlaku di Indonesia. Padahal peraturan perundang-undangan itu tersusun secara hirarkis dan mempunyai proporsi materi muatan tertentu sehingga harus diuji secara konsisten dalam satu lembaga saja agar memberikan suatu kepastian hukum bagi masyarakat.